2014
DOI: 10.24199/j.mmv.2014.71.01
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and migration of planktonic polychaete larvae in Onagawa Bay, north-eastern Japan

Abstract: Abe, H., Sato-Okoshi, W., Nishitani, G. and Endo, Y. 2014. Vertical distribution and migration of planktonic polychaete larvae in Onagawa Bay, north-eastern Japan. Memoirs of Museum Victoria 71: 1-9.The planktonic larvae of polychaetes are one of the most numerous and diverse groups in coastal zooplankton; however, little is known about their larval dynamics and the factors that affect their vertical distribution. We investigated the vertical distribution and migration of planktonic polychaete larvae in Onagaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In the present study, 11 spionid species, Polydora calcarea, Polydora onagawaensis, Dipolydora bidentata, Dipolydora giardi, Boccardiella hamata, Boccardia proboscidea, Boccardia pseudonatrix, Pseudopolydora tsubaki, Carazziella spongilla, Polydorella dawydoffi, and Pseudopolydora achaeta were recorded for the first time from the vicinity of Tokyo Bay, including the Boso and Miura Peninsulas. As almost all of them have been already recorded within Japan (Sato-Okoshi 1999, 2000Sato-Okoshi and Abe 2013;Teramoto et al 2013;Abe et al 2014Abe et al , 2016Yamada and Hoshino 2014;Simon et al 2019), these species were considered to be native to Japan or questionable in origin. It is noteworthy that Boccardia pseudonatrix (Fig.…”
Section: Novel Species Records and Potential Alien Species In Vicinitmentioning
confidence: 99%
“…In the present study, 11 spionid species, Polydora calcarea, Polydora onagawaensis, Dipolydora bidentata, Dipolydora giardi, Boccardiella hamata, Boccardia proboscidea, Boccardia pseudonatrix, Pseudopolydora tsubaki, Carazziella spongilla, Polydorella dawydoffi, and Pseudopolydora achaeta were recorded for the first time from the vicinity of Tokyo Bay, including the Boso and Miura Peninsulas. As almost all of them have been already recorded within Japan (Sato-Okoshi 1999, 2000Sato-Okoshi and Abe 2013;Teramoto et al 2013;Abe et al 2014Abe et al , 2016Yamada and Hoshino 2014;Simon et al 2019), these species were considered to be native to Japan or questionable in origin. It is noteworthy that Boccardia pseudonatrix (Fig.…”
Section: Novel Species Records and Potential Alien Species In Vicinitmentioning
confidence: 99%
“…Omel'yanenko & Kulikova 2002, Abe et al 2014. The plankton will presumably include larvae that may have long or short planktonic phases, but probably more of the former; of the larvae captured off-shore in Onagawa Bay by Abe et al (2014), 3 of the 5 spionids identified to species level are known to produce planktotrophic larvae (Blake & Arnofsky 1999, Teramoto et al 2013, while Polydora uncinata, a species known to produce larvae with short planktonic phases and found wild in this bay (Sato-Okoshi & Abe 2012) were absent. Thus we can predict that in off-shore and near-shore cultures molluscs will be infested primarily by species producing larvae with long planktonic phases.…”
Section: Predictionsmentioning
confidence: 99%
“…Firstly, they are produced by the thousands per brood and should therefore be common components of the plankton. For example, Abe et al (2014) recorded up to 5000 larvae m −3 of P. onagawaensis at up to 5 m depth in Onagawa Bay. Secondly, these larvae usual ly spend 3 to 4 wk in the water column (e.g.…”
Section: Planktotrophymentioning
confidence: 99%
“…In Japan, the morphology of three Pseudopolydora species, P. cf. kempi, P. paucibranchiata (Okuda, 1937), and P. antennata (Claparède, 1869) have been previously reported (Okuda, 1937;Imajima and Hartman, 1964;Sato-Okoshi, 2000) while ecological studies have simply recorded the occurrence of Pseudopolydora reticulata Radashevsky and Hsieh, 2000 from Japan (Abe et al, 2014;Kanaya et al, 2015a, b) without reporting on the morphology of this species in detail. In addition, Pseudopolydora achaeta Radashevsky and Hsieh, 2000 is newly recorded from Japan in the present study.…”
Section: Introductionmentioning
confidence: 97%
“…Pseudopolydora species are also known as common dietary items for fish (Tomiyama et al, 2005(Tomiyama et al, , 2007Tomiyama, 2012) and shorebirds (Wilson, 1994). Planktonic larvae belonging to the genus Pseudopolydora are an important component of coastal meroplanktonic communities (Abe et al, 2011(Abe et al, , 2014Omelyanenko and Kulikova, 2011).…”
Section: Introductionmentioning
confidence: 99%